"Sticker Board Activity" to develop fine motor aspects for early childhood - Cinantya, Celia; Maimunah, Maimunah; Ni'mah, Ainun; Melinda, Nanda (Journal of Early Childhood Care and Education, 2024)
The purpose of this study was to describe the development of Activity Sticker Board media, to analyze the eligibility and effectiveness of media to develop fine motor aspects in sticking pictures properly in early childhood. This study uses the Research & Development method with the ADDIE model. The research subjects were group B children at Tunas Harapan Kindergarten, Hulu Sungai Selatan. Data collection techniques through questionnaires and observation. Data analysis is a descriptive analysis using tables and graphs. The results of this study are the results of the eligibility of the media to get a percentage of 96% with the criteria of very feasible and effective in developing fine motor aspects in sticking pictures correctly by 93% of children getting a Very Good Developed score. The conclusion from this study is that Activity Sticker Board media is considered very eligible and effective in developing fine motor aspects in sticking pictures properly in early childhood. The suggestion for developing this media is to use reusable sticker material so that the media is more durable and can be used long term.